Reengenharia de Processo de Atendimento Odontológico: estudo de caso em uma Clínica Odontológica de Universidade - Thiago Goncalves da Silva Goulart (2021)
A case study was carried out on the care process of the Dental Clinic of the Faculty of Dentistry of the Federal University of Mato Grosso do Sul. Deficiencies in control, digital and computerized interactions were identified, with most of their work operations performed manually. and on paper. In view of the relevance of clinical care for society, as well as its importance in the practical training of dental students, this study consisted of a survey and analysis of the current care process, survey of points for improvement and proposal of a plan of action that contemplates them, together with the addition of information technology, in a new process design. This practice of redesigning a process to improve it using technology is known as Business Process Reengineering (RPN). An action plan was proposed, where suggestions for improvements were listed, involving the use of an information system to optimize the process, removing repetitive and manual tasks and improving its controls.